2012
DOI: 10.1080/13504622.2011.598227
|View full text |Cite
|
Sign up to set email alerts
|

The architecture of children’s relationships with nature: a phenomenographic investigation seen through drawings and written narratives of elementary students

Abstract: How do young children portray and describe their relationships with nature? In what ways do young children's relationships with nature vary by grade level? These two research questions guided this phenomenographic study, which investigated developmental differences in children's relationships with nature. A total of 176 children, aged 6-11, from ten classrooms in grades 1-5 participated and were asked to 'draw pictures of themselves outside doing something and write about their picture and their relationship w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 45 publications
2
44
0
10
Order By: Relevance
“…Regarding environmental valuing, this study also pointed to the students' appreciation of nature as seen before in other studies (Kalvaitis & Monhardt, 2011;Payne, 1998). These students showed high appreciation both towards nature itself but also towards learning activities outdoors.…”
Section: Relationships Between Different Aspects Of Learningsupporting
confidence: 82%
See 2 more Smart Citations
“…Regarding environmental valuing, this study also pointed to the students' appreciation of nature as seen before in other studies (Kalvaitis & Monhardt, 2011;Payne, 1998). These students showed high appreciation both towards nature itself but also towards learning activities outdoors.…”
Section: Relationships Between Different Aspects Of Learningsupporting
confidence: 82%
“…Studies of outdoor environmental education activities focusing on children's relationships with nature indicate that they show positive emotions toward nature (Kalvaitis & Monhardt, 2011;Payne, 1998) as well as develop an environmental ethical awareness and responsibility when encountering nature (Mårtensson et al, 2011;Palmberg & Kuru, 2000). Environmental learning in nature has an impact on emotional and affective growth, as well as on cognitive growth, as shown in a study by Brody (2005).…”
Section: (2) 2013mentioning
confidence: 99%
See 1 more Smart Citation
“…Their research participants were aged between 6 and 11 years of age, and were invited to complete two tasks: draw a picture of themselves in nature; write about their picture and their relationship with nature. Their research found a positive relationship with nature from the participants, but distinctions in the image content depending upon the age of the individual (Kalvaitis and Monhardt, 2012).…”
Section: Arts-based Learningmentioning
confidence: 94%
“…' Kalvaitis and Monhardt (2012) used two research tools for data collection: drawings and narratives. Their research participants were aged between 6 and 11 years of age, and were invited to complete two tasks: draw a picture of themselves in nature; write about their picture and their relationship with nature.…”
Section: Arts-based Learningmentioning
confidence: 99%